(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2008)
Some companies have chosen to implement Environmental Management Systems, under the context of ISO 14000 standards, and not limit themselves only to complying with what is required by legal regulations, thus demonstrating a high degree of involvement with environmental problems. In this exploratory research, the components of these systems (SGA - FONDONORMA) and an overview of international and national figures of ISO 9000 and ISO 14000 certified companies (from the CONIDUSTRIA perspective) are shown. Subsequently, four local experiences of companies committed to the environment are presented, addressing the characterization of their environmental management systems and the benefits that are perceived from their implementation. Underlying this article is the idea that environmental management responds to a dynamic process of overcoming that companies have expressed in their concern to improve the quality of their products, that is how VENEFARO, C.A. COCIPRE, C.A, COVENCAUCHO, S.A. UNITED DISTILLERIES, S.A. companies recognized and certified for the high quality of their products, through a set of measures, actions or practices allow us to obtain a profile of the most proactive local companies with the environment.